1981
DOI: 10.3133/ofr81815
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology of Area 7, Eastern Coal Province, Ohio

Abstract: The U.S. Geological Survey established 24 study areas in the Eastern Appalachian Coal Province to appraise the hydrology and water resources from Alabama to Pennsylvania. Chemical, physical, biological, and streamflow data were collected from 138 synoptic sites in Area 7, eastern Ohio. The data are evaluated and presented in this report. Area 7 lies within the drainage basins of Muskingum, Walhonding, Tuscarawas, and Little Muskingum Rivers and Duck and Wills Creeks in eastern Ohio. Walhonding, Tuscarawas, Lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Detection frequencies and concentrations of inorganic chemicals were consistent with existing monitoring data from the area. , While concentrations of inorganic species in this study were generally below MCLs, exceedances were observed for arsenic (a known carcinogen), barium (a cardiovascular toxicant), nitrate (a probable carcinogen), and lead (a neurotoxicant). Lead was detected frequently in PA (96% of samples), and while lead has a health-based MCL, no concentration of lead is thought to be safe . Some inorganic species varied substantially in detection frequency and concentration by state (e.g., arsenic), which may reflect differences in the mineralogic composition of drinking water aquifers and their overlying sediments, as well as differences in groundwater flow patterns and associated differences in water–rock interaction times. Our results indicate generally either inverse or no associations between concentrations of inorganic chemicals and UOG exposure metrics, even those accounting for hydrogeological pathways.…”
Section: Discussionmentioning
confidence: 71%
“…Detection frequencies and concentrations of inorganic chemicals were consistent with existing monitoring data from the area. , While concentrations of inorganic species in this study were generally below MCLs, exceedances were observed for arsenic (a known carcinogen), barium (a cardiovascular toxicant), nitrate (a probable carcinogen), and lead (a neurotoxicant). Lead was detected frequently in PA (96% of samples), and while lead has a health-based MCL, no concentration of lead is thought to be safe . Some inorganic species varied substantially in detection frequency and concentration by state (e.g., arsenic), which may reflect differences in the mineralogic composition of drinking water aquifers and their overlying sediments, as well as differences in groundwater flow patterns and associated differences in water–rock interaction times. Our results indicate generally either inverse or no associations between concentrations of inorganic chemicals and UOG exposure metrics, even those accounting for hydrogeological pathways.…”
Section: Discussionmentioning
confidence: 71%
“…Total iron concentrations varied over 2 orders of magnitude, from a minimum of 2.9 mg/L at sampling site S2 to 120 mg/L at SI. These values are within the range of concentrations of sulfate and iron from other watersheds in Ohio that are affected by acid mine drainage (Engelke and others, 1981).…”
Section: Water Qualitymentioning
confidence: 67%
“…Aquifers within the study area are comprised of cyclic horizontal sequences of Permian- and Pennsylvanian-age fractured sandstones, siltstones, shale, limestone, and coal, which form repeated heterogeneous perched aquifer systems and crop-line springs (Figure S3). Formations are generally flat-lying with a gentle eastward dip (∼6 m/km), and surface expressions grade from older Pennsylvanian Conemaugh and Monongahela formations in the northwest to younger Permian age materials (Dunkard formation) to the southeast. Erosion has produced a steep rugged topography with deeply incised valleys. Extensive stress-relief fracturing beneath valleys provides pathways for faster groundwater flow. Domestic-well yields in valley settings generally range from (3.1 × 10 –4 )–(3.8 × 10 –4 ) m 3 /s, whereas yields in upland areas vary between 1.2 × 10 –4 and 1.9 × 10 –4 m 3 /s .…”
Section: Study Regionmentioning
confidence: 99%
“…Due to differences in hydrogeologic conditions, geologic provinces (e.g., the highly deformed Appalachian structural front in northeastern Pennsylvania as compared to the minimally deformed Appalachian Plateau to the west), and state regulatory frameworks for drinking-water protection, it is reasonable to expect that groundwater vulnerability to contamination from UOG may differ between the eastern and western portions of the NAB. Moreover, the portions of Ohio and West Virginia that now host UOG extraction have supported extensive surface and subsurface coal mining and conventional oil and gas (COG) development for more than a century. Coal mine discharges have raised concentrations of iron, manganese, sulfate, and toxic metals in the surface waters of the region. , As many as one in five streams in West Virginia have been degraded by coal mining operations, while 1300 miles of streams and rivers in Ohio are formally recognized as impaired. , Similarly, leaks from abandoned COG wells have been cited as potential sources of organic contaminants, heavy metals, brines, and iron to streams and rivers. ,, That these polluted surface waters are hydraulically connected to groundwater suggests that residential water wells may be at risk of contamination by coal mine discharges and COG, although observations appropriate for evaluating these risks are scarce.…”
Section: Introductionmentioning
confidence: 99%